MANAJEMEN KEPEMIMPINAN KEPALA MADRASAH DALAM PEMBINAAN PROFESIONALISME GURU MADRASAH IBTIDAYAH NURUL IMAN DESA KOTASAN - Tri Fajriah Humaira (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
Various studies on the leadership management of madrasah principals in fostering teacher professionalism have actually been carried out in Indonesia. However, in Indonesia it seems that research is being conducted in State Elementary Schools. In line with this information, research that examines the leadership management of madrasah principals in fostering the professionalism of private Madrasah Ibtidaiyah (MIS) teachers has never been carried out. Research like this needs to be done because it can provide information about how the principal or madrasah in managing their leadership optimally in fostering teacher professionalism. In addition, the findings obtained can be used as the basis for development research carried out in management learning. The purpose of this study was to find out how the Leadership Management of the Head of Madrasah in the Professional Development of MIS Teachers Nurul Iman, Kotasan. This study uses a qualitative method with a descriptive approach. From the research that has been carried out by researchers, the results are that (1) Leadership management carried out by the Head of Private Ibtidaiyah Madrasah (MIS) Nurul Iman Kotasan in the Professional Development of Madrasah Teachers is by using Open Management. This is done so that all madrasa parties know and can act more honest and able to solve a problem together; (2) There are still a small number of teachers who still find it difficult to have professional skills in educating students; (3) Head of MIS Nurul Iman Kotasan continues to carry out his leadership management in fostering teachers to become professional teachers in educating students.